Functional effects of operations for malignant gastric neoplasms: prevention, diagnosis and treatment of post-gastrectomy disorders - A. V. Chaika; V. M. Khomyakov; A. B. Ryabov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To highlight the modern concept on the pathogenesis of postgastrectomy disorders and related morbid conditions, approach to their treatment and potential for improvement of postsurgical rehabilitation and quality of life of postsurgical gastric cancer patients. Summary. Surgical treatment of gastric cancer includes complete or partial resection of the organ, its lymphatic system and ligaments that is followed by impairment and reduction of digestive process and is associated to series of disorders, related to altered visceral innervation. Three basic groups of disorders are defined: disorders related to impaired organ anatomy; disorders caused by change in anatomical and physiological interrelations and developing as a compensatory response (mostly of functional origin); metabolic disorders. Development of inflammatory and of fibrotic anastomotic strictures and stenoses, erosions and/or ulcers, as well as obstruction caused by intestinal loop in relation or peritoneal adhesions make conservative treatment ineffective that require endoscopic or open surgical approaches: bougieurage, stenting or surgical reconstruction. Postoperative functional disorders are prone to conservative treatment: lifestyle modification, change in diet composition along with pattern of food intake combined to antisecretory, spasmolytic and prokinetic drugs. Severe functional disorders which do not respond to conservative treatment should be considered as possible indications for surgical treatment. Adequate metabolic correction is required: water and electrolyte disorders should be corrected by intravenous infusion therapy and maintaining of sufficient oral fluid intake; hypoproteinemia requires intake of protein-rich food and satisfactory conditions for its digestion and absorption; iron supplementation should be prescribed for microcytic anemia, as well as cyano- cobalamin for B12-deficiency. Nutritional failure that is frequently combined to above-listed postgastrectomy disorders. Patient requires dietic modification and balanced enteral feeding, combined to increased physical activity. Conclusion. Ultimate goals in treatment of postgastrectomy disorders and their complications in patients after extensive gastrointestinal surgery include improvement in quality of life, social and professional rehabilitation.